Peningkatan Kemampuan Seni Melalui Tari Kreasi Terhadap Anak Usia Dini - Hasra Hasra; Nasaruddin Nasaruddin; Riskal Fitri (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
This study aims to improve early childhood artistic skills through the structured implementation of creative dance activities in Group B at TK Bilingual MICI Al Basit. The background of the research is based on empirical conditions in the field indicating rigid and monotonous art learning, which results in low kinesthetic coordination and aesthetic expression among children. The method used in this study is Classroom Action Research (CAR) conducted in two cycles based on the Kemmis and McTaggart model. Each cycle encompasses four procedural stages: planning, action execution through guided demonstration strategies, observation, and reflection. The research subjects consisted of seven children aged 5–6 years. Data collection techniques were conducted holistically using structured observation sheets and authentic documentation, while data analysis applied a qualitative descriptive approach alongside simple quantitative analysis. The results of the study show a significant and gradual improvement in the children's artistic skills. In the initial condition (pre-action), the children's classical mastery percentage was only 14.28%. After the intervention was provided in Cycle I, the mastery percentage increased to 42.85%. Culminating at the end of Cycle II, the classical mastery percentage soared sharply to reach 85.71%, with the majority of children successfully shifting into the Developing as Expected (BSH) and Developing Very Well (BSB) categories. Qualitatively, the children were able to harmoniously synchronize body movements with the tempo of the music, demonstrate expressive flexibility, and exhibit high self-confidence when performing in groups. Based on these findings, it is concluded that the implementation of play-based creative dance is proven effective in holistically improving early childhood artistic skills and is suitable as an alternative art learning model in early childhood education institutions.